Analisis Tingkat Kesesuaian Tempat Penyimpanan Sementara (TPS) Limbah Bahan Berbahaya dan Beracun (B3) di PT. X - Salsabila, Wiranti; Fadhil, Muhammad Faisal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The handling of Hazardous and Toxic (B3) waste needs a storage system that satisfies technical criteria in an effort to reduce environmental damage and health hazards. This study aims to evaluate the level of compliance of the Temporary Sotrage Area (TPS) for B3 waste at PT. X with the applicable technical requirements. The research was conducted through field observations, measurement of technical parameters, and examination of licensing documents and B3 waste management records. The results indicate that the compliance level of the B3 waste TPS reached 95.88%, and falls into the highest performance category. Several issues were still identified, particularly in the aspects of B3 waste accumulation and the provision of symbols and labels. Therefore, this study recommends the implementation of periodic internal audits and improved compliance with B3 waste packaging and labeling standards.